2021
DOI: 10.1016/j.aninu.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of xylanase and a fermentable xylo-oligosaccharide on performance and ileal digestibility of broiler chickens fed energy and amino acid deficient diets

Abstract: The objective of this study was to evaluate the effect of a product consisting of a combination of xylanase and xylo-oligosaccharide (STBIO) on performance and ileal digestibility of broiler chickens fed energy and amino acid (AA) deficient diets. Day-old male Ross 308 broiler chicks were randomly allocated to 8 pens per treatment, with 25 chicks per pen. Treatments based on wheat-corn-soybean meal diets were arranged in a 3 × 2 factorial design: a positive control that met or exceeded nutrient recommendations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 25 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Corn occupied most of poultry diets contain considerable levels of arabinoxylans as part of non-starch polysaccharides. XOS is more likely to perform as an activator of specific bacteria in the gastrointestinal tract (GIT) than directly act as a quantitative prebiotic, thereby increasing SCFA including butyrate can be helpful to gut health [ 18 , 19 ]. The stimbiotic used in this study was designed to convey XOS to fibrolytic microflora in the large intestine by adding a small portion of ex-vivo produced short-chain XOS with a β-1,4-endo xylanase [ 20 ], which hydrolyzes the arabinoxylan portion in the feed to XOS in the GIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corn occupied most of poultry diets contain considerable levels of arabinoxylans as part of non-starch polysaccharides. XOS is more likely to perform as an activator of specific bacteria in the gastrointestinal tract (GIT) than directly act as a quantitative prebiotic, thereby increasing SCFA including butyrate can be helpful to gut health [ 18 , 19 ]. The stimbiotic used in this study was designed to convey XOS to fibrolytic microflora in the large intestine by adding a small portion of ex-vivo produced short-chain XOS with a β-1,4-endo xylanase [ 20 ], which hydrolyzes the arabinoxylan portion in the feed to XOS in the GIT.…”
Section: Discussionmentioning
confidence: 99%
“…Xylo-oligosaccharides (XOS) produced by exogenous xylanase (EX) acts either directly as a prebiotic or a signalling molecule to stimulate fibre-degrading microbiota and cross-feeding mechanisms [ 17 ]. However, a broiler study reported that the amount of XOS generated by EX is somewhat dependent on the structure of the fibre in the basal diet and often is not sufficient to explain the increased butyrate and other short-chain fatty acids (SCFA) in the caeca [ 18 ]. Ribeiro et al [ 19 ] stated that a small level of XOS is more likely to perform as an activator of specific bacteria in the gastrointestinal tract (GIT) than directly act as a quantitative prebiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no shortage of studies indicating that the exogenous xylanase escalated the nutrient digestibility and growth performance of broilers fed corn basal diets, few speci c enzyme mixtures included debranching enzymes or their transformative effects in vivo were not clear [20,31,34,35]. In the current study, improvements of growth performance in supplementation with EXF might be ascribed to the bene cial bioactivities of feruloylated XOS via prebiotic, immunomodulatory, and/or antioxidant effects [36].…”
Section: Discussionmentioning
confidence: 80%
“…In the presence of the double xylanase, more X 5 and X 6 were manufactured, which likely stimulated the xylandegrading bacteria, but there was insufficient substrate to use, due to the low soluble NSP concentration in the sorghum-based diets (González-Ortiz et al, 2021). It may have been possible that the single xylanase dose induced production of soluble xylan, which provided sufficient fuel for these bacteria, but the double dose and NSPase cocktail produced too much, which had a detrimental impact on microbiota balance and the gastrointestinal environment.…”
Section: Discussionmentioning
confidence: 99%